2020
DOI: 10.1080/10942912.2020.1814323
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characterization and antibiotic resistance of Staphylococcus aureus isolated from traditional cheeses in Turkey

Abstract: This study aimed to provide information about the characteristics of Staphylococcus aureus strains isolated from traditional Turkish cheese samples in Ankara (Turkey), focusing on their prevalence, phenotypic and genotypic characteristics, and antibiotic resistance. To this end, 387 cheese samples were randomly collected from various local bazaars and supermarkets. A total of 85 S. aureus isolates were identified by morphological, biochemical and molecular methods. In addition, the strains were screened for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
3
8
1
Order By: Relevance
“…Rossato et al in Brazil and Kot et al in Poland showed no resistance to vancomycin, linezolid, or teicoplanin (28,29). Also, in a study by Kayili and Sanlibaba in Turkey, no resistance to linezolid was reported in any of the S. aureus strains, but low resistance (18.8%) was observed to vancomycin (30). Fortunately, in our study, all strains of S. aureus were sensitive to vancomycin, linezolid, and teicoplanin.…”
Section: Discussionsupporting
confidence: 54%
“…Rossato et al in Brazil and Kot et al in Poland showed no resistance to vancomycin, linezolid, or teicoplanin (28,29). Also, in a study by Kayili and Sanlibaba in Turkey, no resistance to linezolid was reported in any of the S. aureus strains, but low resistance (18.8%) was observed to vancomycin (30). Fortunately, in our study, all strains of S. aureus were sensitive to vancomycin, linezolid, and teicoplanin.…”
Section: Discussionsupporting
confidence: 54%
“…There are currently few studies focusing on assessing the whole production chain of cheeses from unpasteurized milk [ 4 , 37 , 38 ]. Most studies have focused on the evaluation of S. aureus strains isolated from raw milk from cows with clinical or subclinical mastitis or only in finished products [ 24 , 29 , 39 , 40 , 41 , 42 ]. Nevertheless, estimation of the prevalence and genetic determinants of S. aureus is always important to facilitate the implementation of rational mitigation strategies and to avoid the dissemination of this pathogen through the food chain [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penicillin resistance in S. aureus strains isolated from milk and its byproducts has been detected in several previous studies worldwide (Dittmann et al 2017;Kalayu et al 2020;Liao et al 2018;Mohammed et al 2018;Pekana and Green 2018;Rodrigues et al 2017). A high prevalence of S. aureus resistance to penicillin, ampicillin, erythromycin, tetracycline, and clindamycin was also screened in Brazil and Turkey, which was 77.9%, 68.3%, 65.4%, 24.0%, 19.2% (in milk and Brazilian Coalho cheese samples), and 84.71%, 72.94%, 22.35%, 5.88%, 50.59% (in soft and semisoft ripened Turkish cheese samples), respectively (Kayili and Sanlibaba 2020;Pereira et al 2018). Rodrigues et al (2017) studied the antimicrobial resistance profiles of Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the findings of this study with other studies regarding the occurrence of AMR S. aureus, a Turkish study reported the investigation of S. aureus isolates from 387 traditional cheese samples (White, Tulum, Ezine, and raw sheep milk cheese) showed a high rate of MDR (72.94%). Meanwhile, a Brazilian study found a lower prevalence of S. aureus isolates (29%) (Kayili and Sanlibaba 2020;Pereira et al 2018). Several efflux pump genes are identified as responsible for MDR mechanisms (Mahmood et al 2016;Mbindyo et al 2021).…”
Section: Discussionmentioning
confidence: 99%